“Tudo que nóis tem é nóis”: continuidades históricas do Movimento Negro e do Movimento de Mulheres Negras nas resistências coletivas ao epistemicídio na UFMG - Karina Pereira dos Santos (2021)
The history of the public university has been marked by the emergence of black and anti-epistemicide collectives. In addition to the legislation that institutes affirmative action, the Black Movement (MN) and the Black Women's Movement (MMN) in Brazil have opened paths for the anti-racist struggles that we live in education. The research presented here sought to understand how collectives, groups and the Black Movement UFMG build resistance to epistemicide at the university, contributing to the occupation of black people as subjects of knowledge in this space. The specific objectives of the research were: a) to understand how black collectivities and anti-epistemicide dialogue and tension the epistemologies present in the university; b) identify how they perceive and act on affirmative action policies at UFMG; c) analyze the possible correlation between resistance movements to epistemicide and the permanence of black students; and d) identify and discuss how their practices articulate Afro-Brazilian epistemologies, with regard to ancestry, memory, corporeality and life trajectories. The methodological path consisted of monitoring and in-person and virtual participation in the collective actions of the researched subjects, with the adoption of an ethnography-writing notebook. The researcher's observations, experiences and affections are part of the text. Six collective interviews and one individual were also carried out with members of black and anti-epistemicide communities, including five collectives, a research and extension group, and the Black Movement UFMG. Theoretical dialogues were woven in an interdisciplinary way with references from black and decolonial feminism, from critical psychologies of racism, from studies in the field of education, and from the production of black Brazilian intellectuals whose thought is articulated with the MN and to MMN. As research findings, we highlight that black and anti-epistemicide communities at UFMG have built strategies and tactics to tension the gaps in the curricula through articulations with departments and collegiate bodies, indicating that the absence of black and indigenous authors compromises scientific training generally, not only affecting black people. As for affirmative actions, in addition to the strangeness of the majority presence of non-black people in the composition of the groups, they question the undue occupation of reserved spaces and the insufficiency of institutional policies for permanence. The volume and intensity of reports of racist violence experienced at the university are frightening. Faced with and despite them, collectives, groups and MN UFMG organize various practices, including meetings, seminars, readings and debates, as well as affective events and affirmative parties of black epistemologies. Such practices boost the conditions of possibility for staying at the university as a place of law.